Pengaruh Konseling Terhadap Kepatuhan Ibu Hamil Mengonsumsi Tablet Fe Untuk Mencegah Anemia Selama Kehamilan - Arifin, Hasriany; Warsid, Aisyah; Nirmalarumsari, Chrecencya; Wiansi (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2024)
Anemia is a nutritional problem that often occurs in the world and affects more than 600 million people. The estimated prevalence of anemia in general is around 50%. The World Health Organization (WHO) reports that 40% of maternal deaths in developing countries are related to anemia in pregnancy. This study aims to determine the effect of counseling on pregnant women's compliance with taking Fe tablets to prevent anemia at the East Walenrang Community Health Center. This research design is a pre-experimental design whose design uses the one group pretest-posttest design. This research was conducted at the East Walenrang Community Health Center. The population of this study was 33 pregnant women. Sample of 33 people. The data analysis used was the Wilcoxon test. The research results showed that the p value = 0.000 (p<0.05), this shows that Ha was accepted, which means there was an influence before and after the intervention. The conclusion is that there is an influence of counseling on the compliance of pregnant women in consuming Fe tablets to prevent anemia at the East Walenrang Community Health Center. Advice is given to pregnant women to adhere to taking Fe tablets during pregnancy to prevent anemia.